Evaluasi Morfologi, Produksi dan Kualitas Tumbuhan Asystasia gangetica (L.) T. Anderson pada Lingkungan yang Berbeda: Evaluation of Plant Morphology, Production and Quality of Asystasia gangetica (L.) T. Anderson at Different Environment Condition - Nur Rochmah Kumalasari; Rizal Putra; Luki Abdullah (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2020)
Ara Sungsang (Asystasia gangetica (L.) T. Anderson) is a perennial creeper that grows rapidly and widely in various regions. The aim of this study was to evaluate different environmental condition on plant morphology, biomass production and quality as forage. This research was conducted from August 2017 to March 2018 at Purwakarta, Sumedang, Lebak and Bogor. Morphological traits were observed from 10 different plants while biomass production and nutrient quality were sampled through 4 plots with sample size was 50 cm x 50 cm. The measured parameters were plant length; leaves length, width and number; branches number, fresh and dry weight; and nutrient content. Data were analyzed by ANOVA Matrix Unbalance used software R-3.3.2., then the significant results analyzed by Duncan. The results showed that ara sungsang length was 41-250 cm, branches number was 9-38, leaves number was 39-100, 3-5 cm width and 7-13 cm length. The nutrient analysis resulted that dry matter was 19.84% -26.87%, crude protein was10.90%-35.17%, crude fat was 0.78%-4.71%, crude fiber was 10.22%-48.97% and nitrogen free extract was 31.99%-54.21%